Hydroelectric Power Plant Design with Hydraulic Pump System - Dewn innajie; Coolen Laure; Mecandily Gercia (Newinera Publisher, 2021)
The goal of this research is to develop a small-capacity power generator that may be used as an alternative energy source for home use, particularly in rural regions. The hydraulic ram pump was included in the design as a critical component for extending the duration of power production by turbines and generators, which was achieved via innovative engineering. During the manufacturing of hydraulic ram pumps, there are three test variants, which are comprised of the intake pipe length (2.6m), the output pipe height (2.5m, 3.2m, and 3.7m), and the outlet pipe diameter (3/4